2014
DOI: 10.1112/blms/bdu074
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of diagonal Poisson structures

Abstract: Abstract. The degeneracy locus of a generically symplectic Poisson structure on a Fano manifold is always a singular hypersurface. We prove that there exists just one family of generically symplectic Poisson structures in Fano manifold with cyclic Picard group having a reduced simple normal crossing degeneracy locus.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…(X, ) is simply log-symplectic if moreover D( ) has simple normal crossings, i.e., is a transverse union of smooth components. We note that Lima and Pereira [11] have shown that if (X, ) is simply log-symplectic and X is a Fano manifold of dimension 4 or more with cyclic Picard group, then X is P 2n with a standard (toric) Poisson structure = a i j x i x j ∂ / ∂ x i ∂ / ∂ x j , and x i homogeneous coordinates (and consequently deformations of (X, ) are of the same kind, at least set-theoretically).…”
mentioning
confidence: 72%
“…(X, ) is simply log-symplectic if moreover D( ) has simple normal crossings, i.e., is a transverse union of smooth components. We note that Lima and Pereira [11] have shown that if (X, ) is simply log-symplectic and X is a Fano manifold of dimension 4 or more with cyclic Picard group, then X is P 2n with a standard (toric) Poisson structure = a i j x i x j ∂ / ∂ x i ∂ / ∂ x j , and x i homogeneous coordinates (and consequently deformations of (X, ) are of the same kind, at least set-theoretically).…”
mentioning
confidence: 72%
“…We were dragged into the subject by a desire to better understand previous results, most notably [16] and [53], which we recall below. Further motivation comes from the study of holomorphic Poisson manifolds, see [48,35].…”
Section: Introductionmentioning
confidence: 99%
“…The following types of objects have been studied (in greater generality) by several authors; they were first defined by Goto [Got]. More recently, Gualtieri-Pym [GP13], and Pym [Pym17] have studied log symplectic pairs, as have Lima-Pereira [LP14], and Ran [Ran17]. We will focus on log symplectic pairs (X, Y ) where Y is a simple normal crossings divisor, but we note that this is not required in many of the works that we have mentioned.…”
Section: Log Symplectic Pairsmentioning
confidence: 99%